Thrombocytopenic syndromes in pregnancy. (March 2016) - Yan, Matthew; Malinowski, Ann K; Shehata, Nadine
The physiological changes in pregnancy result in platelet counts that are lower than in nonpregnant women. Consequently, thrombocytopenia is a common finding occurring in 7–12% of pregnant women. Gestational thrombocytopenia, the most common cause of low platelet counts, tends to be mild in most women and does not affect maternal, fetal or neonatal outcomes. Gestational thrombocytopenia needs to be distinguished from other less common causes of isolated thrombocytopenia, such as immune thrombocytopenia, which affects approximately 3% of thrombocytopenic pregnant women and can lead to neonatal thrombocytopenia. Hypertensive disorders of pregnancy and thrombotic microangiopathies are both associated with thrombocytopenia. They share a considerable number of similar characteristics and are associated with significant maternal and neonatal morbidity and rarely mortality. Accurate identification of the aetiology of thrombocytopenia and appropriate management are integral to optimizing the pregnancy, delivery and neonatal outcomes of this population. Clinical cases are described to illustrate the various aetiologies of thrombocytopenia in pregnancy and their treatment.